ANALISIS PENEMPATAN KAPASITOR OPTIMAL PADA PENYULANG SENTRAL GARDU INDUK RANGKAS DENGAN SOFTWARE ETAP 12.6 - Muhamad Alif Fatur Rahman; Mahfudz Shidiq; Teguh Utomo (Jurnal Mahasiswa TEUB, 2023)
Distance between power plant and load, growth in industrial sector, and population growth are several reason for the increase in voltage drop on a distribution electrical system. In some cases, voltage drop that happened sometimes can lead to the voltage drop beyond the specific limit which is 10%. One of the solutions we can use to prevent this is Optimum Capacitor Placement(OCP). OCP is a method which using the capacitor bank to supply the reactive power for the compensate for reactive power due to the load. In this research, the problem refers to Sentral Feeder of GI Rangkas which have 35 Distribution Transformer. Power flow analysis and OCP in this research will be done with the help of ETAP 12.6. in this research the optimation will be performed with maximum load. The result from Power flow analysis shows that at the maximum load, there is 10 buses which the voltage drop beyond the limit, hence OCP will be needed so the voltage drop can rise again beyond the limit of 10%. The OCP on ETAP 12.6. generates 4 bus candidates for the placement of capacitor bank, after 3 400 kVAR capacitor banks installed on STO bus, voltage drops reduces until the point where no buses on this system have voltage drop passing the limit. Power losses on the system also got reduced from 285 kW to 211 kW and 83 kVAR to 62 kVAR. Keywords—Voltage drop, Power flow analysis, Optimum Capacitor Placement(OCP), ETAP 12.6